Legal Compliance of Plastic Bottle Recycling-Based Hydroponic Businesses with Business Licensing Legality: Kepatuhan Hukum Usaha Hidroponik Berbasis Daur Ulang Botol Plastik terhadap Legalitas Perizinan Berusaha - Basuki Babussalam; Ali Imaduddin Futuwwah; Dina Novita (Jurnal Dedikasi Hukum, 2025)
Hydroponic cultivation represents a contemporary agricultural methodology that continues to advance in response to increasing food demand and spatial constraints in metropolitan areas. The hydroponic methodology, which uses a growth substrate different from soil, offers a viable alternative for urban populations to cultivate plants independently in limited land areas. However, increasing environmental concerns, particularly regarding plastic waste management, have catalysed the emergence of recycling-oriented innovations in hydroponic practices. This particular initiative aims to enhance the technical and managerial competencies of stakeholders involved in sustainable hydroponic cultivation through the use of reused plastic bottles as a growth medium. The focus of this initiative is Kampung Urban Care Jagir Wonokromo Surabaya. The comprehensive training offered covers hydroponic cultivation methodologies, the application of recycled tools and materials, as well as appropriate plant care practices. Furthermore, this initiative emphasises improving small business management skills, which include basic financial record-keeping, production planning, and the distribution of hydroponic products. Assessments show substantial progress in the production capabilities and expertise of stakeholders in managing their businesses effectively. Through this initiative, stakeholders have successfully increased production capacity, produced high-quality products, and raised environmental awareness regarding plastic waste management. The anticipated long-term outcome is the establishment of a hydroponic business ecosystem that is increasingly independent, sustainable, and environmentally friendly.   Abstrak Budidaya hidroponik merupakan metode pertanian modern yang terus berkembang sebagai respons terhadap meningkatnya permintaan pangan dan keterbatasan ruang di kawasan perkotaan. Metode hidroponik, yang menggunakan media tanam yang berbeda dari tanah, menawarkan alternatif yang layak bagi penduduk perkotaan untuk menanam tanaman secara mandiri di area lahan yang terbatas. Namun, meningkatnya keprihatinan lingkungan, terutama terkait pengelolaan limbah plastik, telah memicu munculnya inovasi yang berorientasi pada daur ulang dalam praktik hidroponik. Inisiatif ini bertujuan untuk meningkatkan kompetensi teknis dan manajerial para pemangku kepentingan yang terlibat dalam budidaya hidroponik berkelanjutan melalui penggunaan botol plastik bekas sebagai media tanam. Fokus inisiatif ini adalah Kampung Urban Care Jagir Wonokromo Surabaya. Pelatihan komprehensif yang ditawarkan mencakup metode budidaya hidroponik, penerapan alat dan bahan daur ulang, serta praktik perawatan tanaman yang tepat. Selain itu, inisiatif ini menekankan peningkatan keterampilan manajemen usaha kecil, termasuk pencatatan keuangan dasar, perencanaan produksi, dan distribusi produk hidroponik. Penilaian menunjukkan kemajuan yang signifikan dalam kemampuan produksi dan keahlian para pemangku kepentingan dalam mengelola usaha mereka secara efektif. Melalui inisiatif ini, para pemangku kepentingan berhasil meningkatkan kapasitas produksi, menghasilkan produk berkualitas tinggi, dan meningkatkan kesadaran lingkungan terkait pengelolaan limbah plastik. Hasil jangka panjang yang diharapkan adalah pembentukan ekosistem usaha hidroponik yang semakin mandiri, berkelanjutan, dan ramah lingkungan.